Asnaf Care: Satu Strategi Dana Tambahan Lembaga Zakat Negeri Kedah (Lznk) Ketika Pandemik Covid 19 - Mohamad Khadafi Hj. Rofie; Norazita Marina Abdul Aziz; Syahrina bt. Abdullah (USIM Press, 2024)
VOL. 7 NO. 2 (2022) Page (47-55)